2002
DOI: 10.1080/10242430215711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Chiral Discrimination on an Amylose Tris(3,5-dimethylphenyl)carbamate

Abstract: The separation of [2R-[2alpha(R*),3alpha]]-5-[[2-[1-[3,5-bis-(trifluoromethyl)phenyl]ethoxy]-3(S)-4-fluorophenyl)4-morpholinyl]-methyl]-N,N-dimethyl-1H-1,2,3-triazole-4-methanamine hydrochloride from its enantiomer was achieved on an amylose tris-3,5-dimethylphenyl carbamate stationary phase. The retention of the enantiomers is dominated by weak hydrogen bonds while the enantioselectivity is governed by other kinds of interactions, e.g., inclusion in the amylose carbamate chains. Van't Hoffplots of 1nalpha vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Derivatization of polysaccharides with PIC gives the possibility for biopolymer self-interaction via hydrogen bonding through the amide bond of the carbamate under certain solvent conditions [70,71]. We next proceeded to establish that sample aggregation, which could falsely lead to high MW determinations, did not occur with our method.…”
Section: Analyte Aggregationmentioning
confidence: 99%
“…Derivatization of polysaccharides with PIC gives the possibility for biopolymer self-interaction via hydrogen bonding through the amide bond of the carbamate under certain solvent conditions [70,71]. We next proceeded to establish that sample aggregation, which could falsely lead to high MW determinations, did not occur with our method.…”
Section: Analyte Aggregationmentioning
confidence: 99%
“…Based on these spectra, they concluded that the primary interaction between the triazole and the Chiralpak AD stationary phase was a hydrogen bond between the NH group of the triazole moiety and the C=O of the carbamate group of the CSP. However, this proton is involved in a tautomerism, so it is likely that the hydrogen bond may be weaker than normal [54]. As in the case of the cellulosic phase, van't Hoff plots of the traiazole in several hexane/alcohol mobile phases showed a change in slope at about 16 to 20 • C. Also, as before, differential scanning colorimetry (DSC) traces showed an exothermic transition in this same temperature range.…”
Section: Structure and Mechanisms Of Operationmentioning
confidence: 52%
“…In a subsequent study, Bereznitski et al made similar mechanistic studies of ADMPC (Chiralpak AD) [54]. In this case, the primary probe was a complex triazole molecule with three chiral centers, also containing two fluorinated or triflorinated aromatic groups and a teriary amine.…”
Section: Structure and Mechanisms Of Operationmentioning
confidence: 96%
See 2 more Smart Citations